The Influence of Brand Image and Product Innovation on Customer Repurchase Intention through The Mediation of Customer Satisfaction Towards Indomie - Lena Ellitan; Juventino Sindarto; Deatri Arumsari Agung (Journal of Entrepreneurship and Business, 2023)
Purpose: To examine the effect of Indomie's brand image and productinnovation on repurchase intention either directly or throughcustomer satisfaction. Method: This study uses quantitative methods to obtain significantresults and data collection in the form of an online questionnairethrough a google Forms. The total number of respondents obtained was 153respondents with a minimum age of 17 years or more, domiciled inSurabaya, and had consumed Indomie in the last three months. The datawere then analyzed using the structural equation model techniquewith the help of PLS 4 software. Result: The results showed that brand image and product innovationhad a positive and significant impact on customer satisfaction andrepurchase intention, customer satisfaction had a positive andsignificant impact on repurchase intention and consumer satisfactionpartially mediated the relationship between brand image and productinnovation on repurchase intention.